The Strategic Role of Accountants in Promoting Sustainability: An Integrated Approach for Competitive Advantage - Florinel Marian SGÂRDEA; Liviu Marian MATAC; Maria BOLBOCEANU; Paul-Tiberius COMAN (CECCAR Business Review)

(untitled)
Sustainability has become a strategic priority for organizations and governing bodies. Accountants, traditionally seen as financial stewards, have significantly expanded their roles to become strategic leaders in promoting sustainable practices. Their expertise in risk management, financial reporting, and data analysis puts them in a position to influence and shape organizational sustainability strategies. This paper explores how accounting professionals can contribute to sustainability and how to gain competitive advantage. We will examine their contributions at various organizational levels and identify the barriers and challenges they face in this role.